Application of Surfactants in Commercial Crop Production for Water and Nutrient Management in Sandy Soil - Guodong Liu; Monica Ozores-Hampton; Gene McAvoy; Ben Hogue; Crystal A. Snodgrass (EDIS, 2013)
Water-repellent soils are unable to effectively adsorb or retain water. On these soils, water may simply pool on the surface or may move down preferred pathways, leaving large amounts of soil dry even when a large volume of water is applied. Thus, managing water and nutrients in sandy soils is often challenging. This 6-page fact sheet provides an overview of surfactants and how they may be used to better manage water and nutrients in sandy soils for vegetable and fruit production. Written by Guodong Liu, Monica Ozores-Hampton, Gene McAvoy, Ben Hogue, and Crystal A. Snodgrass, and published by the UF Department of Horticultural Sciences, December 2013. http://edis.ifas.ufl.edu/hs1230